It's complicated - Meyers, Nancy; Streep, Meryl; Baldwin, Alec, 1958-; Martin, Steve, 1945-; Krasinski, John, 1979-; Bell, Lake, 1979-; Universal Studios Home Entertainment (Firm) (Universal City, Calif. : Universal Studios Home Entertainment, 2010)
A hilarious look at marriage, divorce and everything in between. With a thriving Santa Barbara bakeshop, a new romance heating up, and her divorce finally behind her, Jane Adler has her life all figured out, until she finds herself trapped between the perfect new beau and her philandering ex-husband who's determined to win her back. When opposites attract all over again, will love be sweeter the second time around? It's...complicated!
Title from web site.
Originally released as a motion picture in 2009.
Special features: "The making of: It's complicated" featurette; feature commentary with producer/writer/director Nancy Meyers, executive producer Suzanne Farwell, director of photography John Toll and editor Joe Hutshing.
Director of photography, John Toll ; editor, Joe Hutshing.
Meryl Streep, Alec Baldwin, Steve Martin, John Krasinski, Lake Bell.
MPAA rating: R; for some drug content and sexuality.
Keywords: Divorced women -- California -- Santa Barbara -- Drama; Bakeries -- California -- Santa Barbara -- Drama; Architects -- California -- Santa Barbara -- Drama; Man-woman relationships -- California -- Santa Barbara -- Drama; Romantic comedy films; Video recordings for the hearing impaired; Feature films; Fiction films